2018
DOI: 10.1091/mbc.e18-02-0079
|View full text |Cite
|
Sign up to set email alerts
|

Constricted migration increases DNA damage and independently represses cell cycle

Abstract: Cell migration through dense tissues or small capillaries can elongate the nucleus and even damage it, and any impact on cell cycle has the potential to affect various processes including carcinogenesis. Here, nuclear rupture and DNA damage increase with constricted migration in different phases of cell cycle—which we show is partially repressed. We study several cancer lines that are contact inhibited or not and that exhibit diverse frequencies of nuclear lamina rupture after migration through small pores. DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
112
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 34 publications
13
112
2
Order By: Relevance
“…In both cases, nuclear membrane ruptures are repaired and generally non-lethal (De Vos et al, 2011;Vargas et al, 2012;Denais et al, 2016;Raab et al, 2016). However, recent studies suggest that loss of nuclear compartmentalization can alter transcription (De Vos et al, 2011), cause mislocalization of large organelles (De Vos et al, 2011;Vargas et al, 2012;Houben et al, 2013), and cause DNA damage (Maciejowski et al, 2015;Denais et al, 2016;Raab et al, 2016;Irianto et al, 2017;Takaki et al, 2017;Pfeifer et al, 2018;Stephens et al, 2019). Based on these data, nuclear membrane rupture is now being evaluated as a major mechanism of genome instability and cell death in lamin-associated diseases and cancer (Isermann and Lammerding, 2017;Houthaeve et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, nuclear membrane ruptures are repaired and generally non-lethal (De Vos et al, 2011;Vargas et al, 2012;Denais et al, 2016;Raab et al, 2016). However, recent studies suggest that loss of nuclear compartmentalization can alter transcription (De Vos et al, 2011), cause mislocalization of large organelles (De Vos et al, 2011;Vargas et al, 2012;Houben et al, 2013), and cause DNA damage (Maciejowski et al, 2015;Denais et al, 2016;Raab et al, 2016;Irianto et al, 2017;Takaki et al, 2017;Pfeifer et al, 2018;Stephens et al, 2019). Based on these data, nuclear membrane rupture is now being evaluated as a major mechanism of genome instability and cell death in lamin-associated diseases and cancer (Isermann and Lammerding, 2017;Houthaeve et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lamin-B filaments are stiff, with a persistence length of ~0.5µm (Turgay et al, 2017), and therefore will not bend and bind a nuclear envelope with high Gaussian curvature, but myosin tension is somehow independently important because pores impose constant curvature. Squeezing of dozens of mobile proteins into low density regions of chromatin could also be relevant and likely explains the large intranuclear accumulations of GFP-53BP1 during migration through narrow channels (Denais et al, 2016;Irianto et al, 2017;Raab et al, 2016) independent of DNA damage Pfeifer et al, 2018). DNA damage is nonetheless consistent with simple orthogonal measures of a bimodal cell cycle delay, illustrating mechanical control of cell cycle as one mechanism of "go-or-grow".…”
Section: Discussionmentioning
confidence: 78%
“…phospho-Histone-2AX). However, parallel quantitation of another DNA damage marker (53BP1) shows no increase Pfeifer et al, 2018), with live-cell imaging of large 'foci' of GFP-53BP1 (Denais et al, 2016;Raab et al, 2016) attributed to generic accumulation of mobile nuclear protein into low density pockets of chromatin (Irianto et al, 2016). Imaging of DNA damage sites indeed remains non-trivial (Britton et al, 2013), and in the particular context of constricted migration γH2AX foci counts appear to increase by only ~50% across cell cycle stages, even when cell cycle is blocked .…”
Section: Introductionmentioning
confidence: 97%
“…Under inflammatory conditions, less traction stress is required for diapedesis, facilitating leukocyte extravasation . Because less traction force is required for transendothelial migration during inflammation, this mechanism may also protect nuclear and DNA integrity, both of which were shown to undergo mechanical damage during invasive migration …”
Section: Mechanical Force In the Service Of Leukocyte Functionmentioning
confidence: 99%
“…9 Because less traction force is required for transendothelial migration during inflammation, this mechanism may also protect nuclear and DNA integrity, both of which were shown to undergo mechanical damage during invasive migration. 65 Accordingly, another recent study demonstrated that T cells can sense 3D environments and density of the collagen matrix. 3D collagen matrices induced methylation of histone 3, lysine 4 residue (H3K4) by methyltransferases, and this methylation increased as a function of collagen density.…”
Section: Force In the Regulation Of Leukocyte Rolling And Diapedesismentioning
confidence: 99%